"Ambulatory Management of Moderate to High Risk COVID-19 Patients: The Coronavirus Related Outpatient Work Navigators (CROWN) Protocol". Issue 1 (February 2021) - Lisker, Gita; Narasimhan, Mangala; Greenberg, Harly; Ramdeo, Ramona; McGinn, Thomas
During the height of the novel 2019 coronavirus disease (COVID-19) pandemic in New York City, area hospitals were filled to 150% capacity, and there was a significant fear among the public of going to the hospital. Many hospitalized patients were treated with therapies that could be administered in a home setting under proper monitoring. We designed the CROWN Program, a Home-Care based ambulatory protocol to evaluate, monitor, and treat moderate to high risk COVID-19 patients in their homes, with escalation to hospital care when necessary. Patients were evaluated with telehealth visits with a Pulmonologist, and a Home-Care protocol, including RN visit, pulse-oximetry, and oxygen, lab-work, intravenous fluids, medication if needed patient data, comorbidities, and symptoms were collected. Labs, including COVID-19 PCR, D Dimer, CRP, Ferritin, Procalcitonin, CBC, and metabolic panel were measured, as were homecare, home oxygen, and intravenous fluids orders, radiographic studies and initiation of an anticoagulant. Emergency Department visits and need for hospital admission during the study period were recorded. A total of 182 patients were enrolled between the start date of April 27th and June 1st, and fell into two categories: not-admitted (101) and post-discharge (81). Two patients were referred for hospital admission, seven were treated and released from the ED, and one was referred to home hospice. There were no unexpected admissions or deaths. The CROWN program has demonstrated the feasibility and apparent safety of a specialized, Home-Care based protocol for the ambulatory management of moderate to high risk COVID-19 patients.